Studies on the magnetoelastic and magnetocaloric properties of Yb1−xMgxMnO3 using neutron diffraction and magnetization measurements. Issue 54 (17th May 2016) - Sattibabu, Bhumireddi; Bhatnagar, A. K.; Vinod, K.; Rayaprol, S.; Mani, Awadhesh; Siruguri, V.; Das, D.
Abstract : We report the magnetic ordering and magnetoelastic coupling of polycrystalline hexagonal Yb1− x Mg x MnO3 ( x = 0.00 and 0.05) compounds by using neutron diffraction measurements. Abstract : We report the magnetic ordering and magnetoelastic coupling of polycrystalline hexagonal Yb1− x Mg x MnO3 ( x = 0.00 and 0.05) compounds by using neutron diffraction measurements. The magnetocaloric properties of these Yb1− x Mg x MnO3 compounds are also studied using magnetization measurements. The temperature dependence of the lattice parameters ( a and c / a ratio) and unit cell volume V show anomalous behavior near T N1 ∼ 85 K (the Mn ordering temperature) due to the magnetoelastic effect. Also all the Mn–O bond distances display considerable variation at T N1 . Isothermal magnetization curves measured near the Yb long range ordering temperatures indicate a field induced magnetic transition with applied field. The isothermal magnetic entropy change (−Δ S M ) is calculated from the magnetization curves measured for different temperatures. Values of maximum entropy change (−Δ S maxM), the adiabatic temperature change (Δ T ad ) and the relative cooling power (RCP) for these compounds are found to be 3.02 ± 0.37 J mol −1 K −1, 8.6 ± 0.95 K and 41 ± 9 J mol −1 for x = 0.00, and 2.63 ± 0.36 J mol −1 K −1, 9.06 ± 0.96 K and 40.0 ± 10 J mol −1 for x = 0.05, respectively, for Δ H = 100 kOe. Rescaling of the −Δ S M vs. T curves for various fields fit into a single curve, implying the second-order phase transition.